The Artistic Character-Stereotype and the Problem of Authorship - Safronova, Lyudmila (Respectus Philologicus, 2006)
The article analyses modern author technologies and imagecharacters that are adequate to the mass reader's demand. It is the mechanisation of the creative process, calculation of optimal plot schemes on the basis of standard character functions, their stereotypification, calculation of a target audience, and calculation of optimal author models in the text. Stereotypification allows us "to form" the mass reader with the preset properties. B. Akunin uses stereotypification but simultaneously subjects it to deconstruction. The writer shows how, through the perception of a character stereotype that has been made natural, the reader identifying with it should fall into the imaginary "correctness" of one or the other ideology. Showing the latent techniques of pre-election technologies, Akunin describes in detail how the image-character is projected onto the promoted ideology; archetypes and stereotypes already existing in the consciousness are taken as base models. Thus, the communicative stereotype generated from an archetype determines the "agreeing" behaviour which regulates social processes.
Keywords: the author; the character; a stereotype; an archetype; identification; target group